Islamisasi Pulau Jawa dalam Perspektif Asimilasi Budaya - Naja, Anang Darun (JOIES (Journal of Islamic Education Studies), 2017)
Today, Islamic education is confronted with a very urgent situation, in which many faces of Islam that emerge are hard, forceful, and do not want to accept differences, this is very contrary to the socio-culture and geographical area of Indonesian society which is very diverse. Therefore, today the face of education in accordance with what has been taught by our predecessors in spreading religion in the archipelago is very necessary to be applied in the world of education. The author suggests that the pattern of teaching peace education that respects the diversity of the Indonesian people really needs to be applied on a massive scale.